Educational Media Related to Nutrition and Fluids for Patients with Chronic Kidney Failure: Literature Review - Herlina Tiwa; Erna Rochmawati (STIKep PPNI Jawa Barat, 2022)
Aim: This review aims to identify and analyze the existing literature related to educational media regarding the provision of nutrition and fluid education in patients with kidney failure Methdos :This research is a literature review approach where the research sources are taken from two databases, namely Pubmed and Google Scholar.Articles were screened using inclusion criteria published in 2015-2021, in the form of journals, English and Indonesian, quasi-experimental research designs and True Experiments, so that six suitable articles were found. The keywords used were “Nutrition Education OR fluid education AND Kidney Failure OR Chronic Kidney Failure; “Chronic Kidney Failure” AND Education on Nutrition and Fluids AND Educational Media”. Results : Of the 2,203 articles that meet the requirements as many as 6 articles. The results of the review show that various media are used for health education related to nutrition and fluids in patients with kidney failure. The media used from simple ones such as booklets to complex applications such as audio-visual media for health education about diet in the intervention group with various media showed significant results compared to the control group. From the results of the review, it was found that simple to complex educational media showed a significant influence on the patient's fluid intake, the patient's quality of life, thereby improving the quality of life. Conclusions : Health education with various educational media can improve dietary compliance of CKD patient, so that nurses are expected to be able to apply various educational media, so that they can meet the nutritional and fluid intake needs of patients with chronic kidney failure.